PENGARUH KOMPLEKSITAS TUGAS, INDEPENDENSI DAN KOMITMEN PROFESIONAL PADA KUALITAS AUDIT - Natawirani, Putu Ratih; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This study aimed to get empirical evidence about the effect of task complexity on audit quality, independence effect on audit quality and influence of professional commitment to audit quality. This research was conducted in the Public Accounting Firm (KAP) of Bali which is registered in the Directory Indonesian Institute of Accountants (Certified) in 2016. Data collection methods used in this research is survey method with questionnaire technique. The population in this study were all auditors working in the public accounting firm of Bali Province by the number of respondents was 45 auditors. The sampling method used is non-probability sampling method with saturated sampling technique. The data analysis used is multiple linear regression analysis. The analysis shows that the complexity of the task negative effect on audit quality, independence, positive effect on audit quality and professional commitment to positive effect on audit quality.
Keywords: task complexity, independence, professional commitment, quality audit